HIV Pre-exposure Prophylaxis Uptake and Continuation Among Key Populations in Cameroon: Lessons Learned From the CHAMP Program. (1st September 2022) - Ndenkeh, Jackson Jr Nforbewing; Bowring, Anna L.; Njindam, Iliassou Mfochive; Folem, Romeo Dongfack; Fako, Guy Christian Hendji; Ngueguim, Florent Gnintedem; Gayou, Oscar Leyou; Lepawa, Kelly; Minka, Christine Minka; Batoum, Christine Manyo; Georges, Sandra; Temgoua, Edith; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Introduction: Pre-exposure prophylaxis (PrEP) is proven to be a highly effective HIV prevention method for key populations. However, its scale-up in resource-limited settings remains suboptimal. This paper seeks to describe PrEP initiation and continuation among key populations in Cameroon. Methodology: From June 2019 through October 2020, we collected routine program data on PrEP uptake and continuation among female sex workers (FSWs) and men who have sex with men (MSM) in the Continuum of prevention, care and treatment of HIV/AIDS with Most-at-risk Populations (CHAMP) program in Cameroon. PrEP was offered to clients who tested negative for HIV and were assessed to potentially benefit from PrEP. Using survival analysis, we identified factors associated with PrEP discontinuation over time with significance set at 5%. Results: Overall, 27, 750 clients were sensitized for PrEP of whom 3, 138 persons were eligible to start PrEP and 1, 409 (45%; FSW: 691 and MSM: 718) initiated PrEP. The PrEP continuation rate was 37% at 3 months, 28% at 6 months and 19% at 12 months. PrEP discontinuation was significantly higher among FSW than MSM [adjusted hazard ratio (aHR) 1.5 (95% CI: 1.2 to 1.9)] in Yaounde [aHR 1.5 (95% CI: 1.2 to 1.9)] and Bafoussam/Bertoua [aHR 3.1 (2.2–4.5)] relative to Douala. Discontinuation was lower among those with moderate [aHR 0.3 (0.3–0.4)] or good adherence [aHR 0.4 (0.3–0.6)] compared with poor adherence (all P < 0.001). Conclusion: Differentiated approaches to deliver PrEP, create demand, and provide more intensive support for adherence and continuation may support scale-up of PrEP in Cameroon for equitable and prolonged impact on HIV prevention.